Health advocacy - a strategy to health promotion - Canel, Regina Célia; Castro, Cláudio Gastão Junqueira de (Journal of Health Law, 2008)
The concept of Health Promotion has been developed approximately thirty years ago and it is already well constructed. Currently, it is very important to develop strategies for its implementation. This article is a reflection on the practice of the Health Advocacy as a strategy for the implementation of the principles and guidelines of the Health Promotion. This works starts questioning how to conciliate conceptual and methodological aspects of the Health Promotion, considering our reality. The main conclusion points to a proposal to develop a "Health Promotion Advocacy.